METODE PENANAMAN NILAI MORAL UNTUK ANAK USIA DINI - Murdiono, Mukhamad (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
This study was intended to describe the instilling of moral values at assigned kindergartens of ’Aisyiyah Bustanul Athfal’ in Yogyakarta City. The description was expected to picture the method that influenced moral education to be chosen for the appreciative instilling of early childhood. The subjects of the study consisted of teachers at five Aisyiyah Bustanul Athfal (ABA) Muhammadiyah kindergartens covering: TK ABA Gedongkiwo, TK ABA Karangkajen, TK ABA Karangkunthi, TK ABA Pandeyan II, and TK ABA Karanganyar. Data were gathered by observation, interview, and documentation. Authenticity probing techniques were utilized as triangulation. The results indicated that methods of moral value education were: story telling, play, field trip, singing, out bond, inuring, figure of speech, poem, and discussion. One method which was usually being utilized was relating and inuring. Instilling methods indicated that moral teaching apparently led to students’ behavioural change, from one inauspicious to turning good. Faced constraints in performing moral point instilling covered: its reducing of gnostic deep relates and its reducing media to be utilized for deep relates, and inconsistencies which often happened between what the teacher did at school and what other elders did at home of in the surrounding environments